Investigation of optical and spectroscopic properties of neodymium doped oxyfluoro-titania-phosphate glasses for laser applications. (15th March 2019) - Neelima, G.; Venkata Krishnaiah, K.; Ravi, N.; Suresh, K.; Tyagarajan, K.; Jayachandra Prasad, T.
Abstract: Nd 3+ -doped oxyfluoro-titania-phosphate glasses with a chemical combination, P2 O5 –CaF2 –BaF2 –TiO2 –Nd2 O3 (PCfBfTiNd), were synthesized by the regular melt-quenching method. These glass samples were investigated through optical absorption, emission, decay curves and spectroscopic ellipsometry analysis. Non-linear refractive index (n2 ) is evaluated using the Boling method and it was found to be as low as 3.68 × 10 −16 cm 2 /W (1.36 × 10 −13 esu). Emission spectra of Nd 3+ -doped glasses were obtained by laser excitation at a wavelength of 808 nm. Results were endorsed that the 0.5 mol% Nd 3+ -doped PCfBfTiNd05 glass could be a suitable gain media for the development of high-energy high-peak power lasers. Graphical abstract: Unlabelled Image